Somatotype and body composition of under-19 women Brazilian beach volleyball players in relation to playing function - Araripe Medeiros, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The athletes` anthropometric and physical characteristics may be a determining factor for success in any sport (GUALDI-RUSSO e ZACCAGNI, 2001). However, so far most studies available in specialized literature concerning beach volleyball have focused in adult categories. Therefore, the purpose of this study was to compare body composition and somatotype of under-19 women beach volleyball players according to their playing function (blocker versus defender). Methods: Twenty-two under-19 women Brazilian beach volleyball players were analyzed. Ten were blockers (aged 17.4±0.7 years) and twelve were defenders (aged 17.2±0.6 years). The players were compared according to their playing position, contrasting the blocker and defender specialists. Measures included height, obtained by a stadiometer (Sanny) with an accuracy of 0.1cm, and body mass, recorded by a portable scale (G-TECH), accurate to 100g. Percentage body fat was assessed using skinfold measures of seven sites applying Cescorf skinfold callipers and the Mcardle et al. (1998) skinfold equation. Somatotypes were calculated using the Heath-Carter method (CARTER e HEATH, 1990). Descriptive statistics were calculated and Mann-Whitney test was used to determine differences between groups (blockers and defenders). SPSS version 19.0 was used for all analyses. Results: Blockers were significantly taller (1.73±3 m versus 1.65±4.5 m) and heavier (63.1±7.6 kg versus 58±7.5 kg) than defenders (p.0.05). As for body composition, no significant differences were found between blockers (20.0±3.6 %) and defenders (19.1±2.8 %). Blockers and defenders were classified according to somatotype as being mesomorph-endomorph (4.8-5.7-3.3 and 4.9-5.8-2.3 respectively). Blockers were significantly more ectomorph than defenders (3.3 and 2.6 respectively). Conclusion: Blockers were significantly taller and heavier than the defenders. Blockers and defenders tend to be endomorph-mesomorph. These results indicate that anthropometric characteristics may be an important tool in the process of talent selection.